Heralds of Future Volcanism: Swarms of Microseismicity Beneath the Submarine Kolumbo Volcano Indicate Opening of Near‐Vertical Fractures Exploited by Ascending Melts. (6th July 2022) - Schmid, F.; Petersen, G.; Hooft, E.; Paulatto, M.; Chrapkiewicz, K.; Hensch, M.; Dahm, T.
Abstract: The Kolumbo submarine volcano in the southern Aegean (Greece) is associated with repeated seismic unrest since at least two decades and the causes of this unrest are poorly understood. We present a ten‐month long microseismicity data set for the period 2006–2007. The majority of earthquakes cluster in a cone‐shaped portion of the crust below Kolumbo. The tip of this cone coincides with a low Vp‐anomaly at 2–4 km depth, which is interpreted as a crustal melt reservoir. Our data set includes several earthquake swarms, of which we analyze the four with the highest events numbers in detail. Together the swarms form a zone of fracturing elongated in the SW‐NE direction, parallel to major regional faults. All four swarms show a general upward migration of hypocenters and the cracking front propagates unusually fast, compared to swarms in other volcanic areas. We conclude that the swarm seismicity is most likely triggered by a combination of pore‐pressure perturbations and the re‐distribution of elastic stresses. Fluid pressure perturbations are induced likely by obstructions in the melt conduits in a rheologically strong layer between 6 and 9 km depth. We conclude that the zone of fractures below Kolumbo is exploited by melts ascending from the mantle and filling the crustal melt reservoir. Together with the recurring seismic unrest, our study suggests that a future eruption is probable and monitoring of the Kolumbo volcanic system is highly advisable. Key Points: Seismicity is clustered in a cone‐shaped volume beneath Kolumbo; the cone's tip coincides with a melt reservoir at 2–4 km depth Seismicity swarms occupy nearby, yet different portions of the crust, ruling out an origin on a single fault Swarms were likely triggered by a combination of fluid pressure perturbations and redistribution of elastic stresses